PENGARUH MODEL GAME BASED LEARNING MENGGUNAKAN APLIKASI QUIZIZZ TERHADAP MINAT DAN HASIL BELAJAR MATEMATIKA SISWA - Dhuha, Shela Hadri Dhuha; Kurniati, Nani; Lu’luilmaknun, Ulfa; Soepriyanto, Harry (FKIP Universitas Mataram, 2024)
The purpose of this study is to determine how the Game Based Learning model using the Quizizz application influences the interests and learning outcomes of grade VIII students of SMPN 3 Jonggat in the 2024/2025 academic year. The results of the Manova analysis obtained a significance value of 0.002 < 0.05, which means that H1 is accepted or there is a difference in the average interest and mathematics learning outcomes of students in the experimental class who use the game based learning model with the Quizizz application and the control class who use the conventional model. The results of the t test show a significance value of 0.006 < 0.05, which means that H1 is accepted or there is a difference in the average learning interest of the experimental class and the control class with the average value of the experimental class being 72.25, which is higher than the control class, namely 70.65. Likewise, there is a difference in the average mathematics learning outcomes of experimental class students, which is higher than that of the control class, with the average score of the experimental class being 85.01, which is higher than the control class, namely 71.35. Because there is a difference between the average of the experimental class and the control class and the average score of the experimental class is superior to the control class, there is an influence of the use of the game based learning model using the Quizizz application on the interest and learning outcomes in mathematics for class VIII students at SMPN 3 JONGGAT for the 2024/2025 academic year.